Identification of Putative Candidate Genes for Water Stress Tolerance in Canola (Brassica napus) - Zhang, Jing; Mason, Annaliese S.; Wu, Jian; Liu, Sheng; Zhang, Xuechen; Luo, Tao; Redden, Robert; Batley, Jacqueline; Hu, Liyong; Yan, Guijun (Frontiers in Plant Science, 2015)
Drought stress can directly inhibit seedling establishment in canola (Brassica napus), resulting in lower plant densities and reduced yields. To dissect this complex trait, 140 B. napus accessions were phenotyped under normal (0.0 MPa, S0) and water-stressed conditions simulated by polyethylene glycol (PEG) 6000 (–0.5 MPa, S5) in a hydroponic system. Phenotypic variation and heritability indicated that the root to shoot length ratio was a reliable indicator for water stress tolerance. Thereafter, 66 accessions (16 water stress tolerant, 34 moderate and 16 sensitive lines) were genotyped using 25,495 Brassica single nucleotide polymorphisms. Genome-wide association studies identified 16 loci significantly associated with water stress response. Two B. napus accessions were used for RNA-seq, with differentially-expressed genes under normal and water-stressed conditions examined. By combining differentially-expressed genes detected by RNA-seq with significantly associated loci from genome-wide association studies, 79 candidate genes were identified, of which eight were putatively associated with drought tolerance based on gene ontology of Arabidopsis. Functional validation of these genes may confirm key drought-related genes for selection and breeding in B. napus. Our results provide insight into the genetic basis of water stress tolerance in canola.